Metagenomic evaluation of food hygiene practices in the National School Nutrition Programme in KwaZulu Natal, South Africa - Sithembile S. Madlala; Nokuthula Mchunu; Monica Dalasile; Rian Pierneef; Poovendhree Reddy (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2025)
Background: The National School Nutrition Programme (NSNP) provides meals to schools in low-income areas in South Africa, implemented by the Department of Basic Education (DBE) with food safety monitored by Municipal Health Services.